Modeling of Long-Range Intra- and Inter-Species Charged Particle Collisions for PIC Simulations (Communications in Computational Physics, 2010)
In this paper we present the modelling of elastic intra-species electron-electronand inter-species electron-ion scattering in a plasma on the basis of the Fokker-Planckcollision operator. Taking into account the equivalence of this operator with astochastic differential equation, we propose a Particle-in-Cell based approach for thenumerical solution of the Fokker-Planck collision term. As we will see, the introducednumerical concept allows the simulation of the collisional relaxation process in a fullyself-consistent fashion.